Popular music heritage, cultural justice and the deindustrialising city - Baker, Sarah, 1977- 1977- (Cambridge elements : elements in music and the city, 2023)
The celebration of popular music can be an important mode of cultural expression and a source of pride for urban communities. This Element analyses the capacity for popular music heritage to enact cultural justice in the deindustrialising cities of Wollongong, Australia; Detroit, USA; and Birmingham, UK. The Element develops a critical approach to cultural justice for examining music and the city in a heritage context and outlines how the quest for cultural justice manifests in three key ways: collection, preservation and archiving; curation, storytelling and heritage interpretation; and mobilising communities for collective action